The addition of curcumin to the diet of post-weaning dairy calves: effects on ruminal fermentation, immunological, and oxidative responses - Novakoski P.V.* (2024)
© The Author(s), under exclusive licence to Springer Nature B.V. 2024.Incorporating Curcumin into animal diets holds significant promise for enhancing both animal health and productivity, with demonstrated positive impacts on antioxidant activity, anti-microbial responses. Therefore, this study aimed to determine whether adding Curcumin to the diet of dairy calves would influence ruminal fermentation, hematologic, immunological, oxidative, and metabolism variables. Fourteen Jersey calves were divided into a control group (GCON) and a treatment group (GTRA). The animals in the GTRA received a diet containing 65.1 mg/kg of dry matter (DM) Curcumin (74% purity) for an experimental period of 90 days. Blood samples were collected on days 0, 15, 45, and 90. Serum levels of total protein and globulins were higher in the GTRA group (P < 0.05) than the GCON group. In the GTRA group, there was a reduction in pro-inflammatory cytokines (IL-1ß and IL-6) (P < 0.05) and an increase in IL-10 (which acts on anti-inflammatory responses) (P < 0.05) when compared to the GCON. There was a significantly higher (P < 0.05) concentration of immunoglobulin A (IgA) in the serum of the GTRA than the GCON. A Treatment × Day interaction was observed for haptoglobin levels, which were higher on day 90 in animals that consumed Curcumin than the GCON (P < 0.05). The catalase and superoxide dismutase activities were significantly higher (P < 0.05) in GTRA, reducing lipid peroxidation when compared to the GCONT. Hematologic variables did not differ significantly between groups. Among the metabolic variables, only urea was higher in the GTRA group when compared to the GCON. Body weight and feed efficiency did not differ between groups (meaning the percentage of apparent digestibility of dry matter, crude protein, and acid detergent fiber (ADF) and neutral detergent fiber (NDF). There was a tendency (P = 0.09) for treatment effect and a treatment x day interaction (P = 0.05) for levels of short-chain fatty acids in rumen fluid, being lower in animals that consumed curcumin. There was a treatment vs. day interaction (P < 0.05) for the concentration of acetate in the rumen fluid (i.e., on day 45, had a reduction in acetate; on day 90, values were higher in the GTRA group when compared to the GCON). We conclude that there was no evidence in the results from this preliminary trial that Curcumin in the diet of dairy calves interfered with feed digestibility. Curcumin may have potential antioxidant, anti-inflammatory, and immune effects that may be desirable for the production system of dairy calves.